On General Integral Operator of Analytic Functions - Nasser Alkasbi; Maslina Darus (Abstract and Applied Analysis)
Let be the integral operator defined by , where each of the functions and is, respectively, analytic functions and functions with positive real part defined in the open unit disk for all . The object of this paper is to obtain several univalence conditions for this integral operator. Our main results contain some interesting corollaries as special cases.